2002
DOI: 10.1074/jbc.m109141200
|View full text |Cite
|
Sign up to set email alerts
|

Permissive Effect of Voltage on mGlu 7 Receptor Subtype Signaling in Neurons

Abstract: G protein-coupled receptors mobilize neuronal signaling cascades which until now have not been shown to depend on the state of membrane depolarization. Thus we have previously shown that the metabotropic glutamate receptor type 7 (mGlu7 receptor) blocks P/Q-type Ca 2؉ channels via activation of a G o protein and PKC, in cerebellar granule cells. We show here that the transient depolarizations used to evoke the studied Ca 2؉ current were indeed permissive to activate this pathway by a mGlu7 receptor agonist. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…The facilitation of extinction acquisition mediated by AMN082, besides being possibly due to an activity-dependent depression of neurotransmission (Perroy et al., 2002; Ugolini et al., 2008), could also be ascribed to a functional blockade of mGlu7 receptors. In fact, it has been shown that AMN082 in addition to stimulating can induce the internalization of mGlu7 receptors (Pelkey et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The facilitation of extinction acquisition mediated by AMN082, besides being possibly due to an activity-dependent depression of neurotransmission (Perroy et al., 2002; Ugolini et al., 2008), could also be ascribed to a functional blockade of mGlu7 receptors. In fact, it has been shown that AMN082 in addition to stimulating can induce the internalization of mGlu7 receptors (Pelkey et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that depolarization per se during agonist exposure can be of relevance for GPCR signalling. Depolarization may weaken the signalling (Brody & Yue, 2000; Ilouz et al ., 1999; Stefani et al ., 1998) or strengthen it (Perroy et al ., 2002). Modulation of pharmacological properties due to receptor localization which might involve interaction with different protein binding partners has also been described (Davare et al ., 2001; Tabata et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mGluR7 directly interacts with the PKC scaffolding protein PICK1, and this interaction along with PKC activity is necessary for mGluR7‐mediated depression of release from cerebellar granule cells (Boudin et al 2000; Dev et al 2000; El Far et al 2000; Perroy et al 2002 a ; Enz & Croci, 2003). Most interestingly, PKC acting downstream of mGluR7 activation has been reported to persistently depress P/Q‐type voltage‐gated calcium channels (VGCCs; Perroy et al 2000, 2002 b ). Similarly, using combined electrophysiological recording and two‐photon Ca 2+ imaging techniques, we recently found that presynaptic MF–SLIN LTD is ultimately expressed as a persistent reduction in P/Q‐type VGCC function (Fig.…”
Section: The Role Of Mglur7 In Presynaptic Mf–slin Ltdmentioning
confidence: 99%